2016
DOI: 10.3390/f7020028
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Climate Change in Swedish Forestry

Abstract: Adaptation to climate change in forestry has become a growing concern, in part due to the impact of storms and other events that have raised the awareness of such risks amongst forest owners. Sweden is one of Europe's most densely-forested countries, with this sector playing a major role economically. However adaptation has, to a large extent, been limited to the provision of recommendations to forest managers, most of which have only been partially implemented. This paper summarizes research with direct impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 81 publications
3
40
0
Order By: Relevance
“…This situation is the paragon of reactive adaptations, defined by Adger et al (2005) as "adjustments in ecological, social, or economic systems in response to observed or expected changes in climatic stimuli and their effects." As found in the literature, the experience of a natural disaster enhances risk perception (Berrang-Ford et al 2011;Rey-Valette et al 2012;Keskitalo et al 2016). In line with this, interviewees generally evoked the exceptional heat waves experienced in 2003 as well as the devastating Lothar and Martin windstorms (in 1999 and 2009, respectively).…”
Section: Climate Change Adaptation: Reaction Firstsupporting
confidence: 72%
See 1 more Smart Citation
“…This situation is the paragon of reactive adaptations, defined by Adger et al (2005) as "adjustments in ecological, social, or economic systems in response to observed or expected changes in climatic stimuli and their effects." As found in the literature, the experience of a natural disaster enhances risk perception (Berrang-Ford et al 2011;Rey-Valette et al 2012;Keskitalo et al 2016). In line with this, interviewees generally evoked the exceptional heat waves experienced in 2003 as well as the devastating Lothar and Martin windstorms (in 1999 and 2009, respectively).…”
Section: Climate Change Adaptation: Reaction Firstsupporting
confidence: 72%
“…Among the many technical, organizational, and economic adaptations found in the literature, the interviews showed that only some of them were implemented in the Vosges and Landes regions. In the two French study cases, implementation focused on technical changes fostering timber production and considered ecological processes to be instrumental features of forestry, a finding similar to what has been observed in the Swedish, Australian or Canadian forest sectors (Keskitalo et al 2016;Keenan 2017;Williamson et al 2019).…”
Section: Resultssupporting
confidence: 54%
“…This guidance notes that temperatures in southern Sweden in 50-80 years will be similar to current temperatures south of the Baltic Sea, while temperatures in northern Sweden will be similar to those 500-1000 km to the south, as climate zones move northwards by some 5-10 km/year [73]. As a result, a number of measures are listed.…”
Section: Development Of Adaptation Policy Within Forestry and Relatedmentioning
confidence: 99%
“…Therefore, it is important to test adaptation capacity of transferred seedlots, which can be a tool to supplement local seed sources in the future [5]. Identification of both productive and robust provenances for utilisation in different climatic environments is in the focus of genetic adaptation to climate change [6]. The regeneration of Norway spruce almost exclusively by planting implies the importance of the adaptation of selected populations to their target planting locations through breeding and selection, thus reducing the potential risks for initial investments in stand establishment [7,8].…”
Section: Introductionmentioning
confidence: 99%